IDDAH DAN IHDAD WANITA KARIER DALAM PERSPEKTIF SYARIAT ISLAM - Andi Herawati; Mukhlis Mukhtar (Jurusan Pendidikan Pancasila dan Kewarganegaraan (PPKn), 2022)
Abstract: Islamic law stipulates the iddah period for a woman whose husband divorced her for three menstrual periods, while the iddah period for a woman whose husband died for four months and ten days. During the iddah (waiting period), women must perform ihdad, which means limiting themselves in activities outside the home, making up or preening. The rules of Islamic law must be obeyed and implemented by women who have been divorced or abandoned by their husbands. This regulation will be a big problem when faced with women who have to work to provide for themselves, their children and their families. Conditions or circumstances like this are categorized by the scholars as an emergency, there is an urgent need (urgent need), or there is a syar'i excuse (a condition that cannot be avoided so that Islamic law cannot be implemented), so they allow women, especially career women, to do activities outside the home. and preening that is not excessive.